Day-night variation in fatty acids and lipids biosynthesis in sunflower seeds - Pleite, Rafael (2008)
It is well known that fatty acid biosynthesis in leaves is closely related to photosynthesis; although a residual synthesis is also detected at night. But less known is the effect of the day-night cycle in fatty acid biosynthesis in heterotrophic tissues such as developing seeds. Through the use of radioactive precursors, we detected variations in the metabolism of fatty acids and lipids during the day-night period in sunflower (Helianthus annuus L.) seeds. These oscillations have been observed both in the fatty acids bound to triacylglycerols and in polar lipids, indicating a fine regulation of the lipids biosynthetic activities in sunflower developing seeds. Additionally, in the triacylglycerol fraction, periodic variations were observed in the oleic and linoleic acids content as a consequence of qualitative variations in the biosynthetic machinery during the day-night period related to temperature changes. Analyzing the rate of oleic acid desaturation, we observed a significant increase in activity in the middle of the night, indicative of the importance of nocturnal desaturation. Similar variations were also observed in the stearoyl-acyl carrier protein (ACP) desaturase activity. This study has shown the variation in the lipid biosynthetic capacity in sunflower developing seeds during the day-night cycle - including control over individual enzymes such as the stearoyl-ACP desaturase-and the influence of diurnal and nocturnal temperatures in the quality (oleic/linoleic ratio) of the oil.